Implementing Differentiated Learning Strategies to Address Individual Learning Needs in Indonesian Vocational High School - Efendi, Asip; Hamidah, Hamidah; Sampurna, Azet; tobib, Ahmad syafak khoirut; Zulaikhah, Siti; Rahmatika, Ratu Vina (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
Differentiated learning was an innovative educational approach aimed at meeting the learning needs of each student according to their characteristics, potential, and learning styles. In modern education, students had varying levels of readiness, interests, and cognitive profiles, which required teaching strategies to be flexible and adaptive. The purpose of this study was to examine the effectiveness of differentiated learning strategies in improving student learning outcomes and engagement. This research employed a qualitative method with a case study approach conducted in several schools that had implemented differentiated learning. Data were collected through observations, interviews with teachers and students, and analysis of instructional documents. Thematic analysis was used to explore how differentiation strategies were applied and their impact on the learning process. The results showed that well-implemented differentiated learning strategies enhanced students’ motivation, conceptual understanding, and active participation in the classroom. Teachers who applied these strategies were better able to adapt learning content, processes, and products to accommodate students’ unique needs, leading to a more inclusive and effective learning environment. In conclusion, differentiated learning proved to be an effective method for addressing individual learning needs and improving educational quality. Therefore, educators required ongoing training and support to design and implement differentiation strategies effectively across diverse educational contexts.